DFT Study for the Spectroscopic and Structural Analysis of p-Dimethylaminoazobenzene - Majid Ali; Asim Mansha; Sadia Asim; Muhammad Zahid; Muhammad Usman; Narmeen Ali (Journal of Spectroscopy)
The study under consideration represents the computational calculations of Azo-based direct dye named p-(dimethylamino)azobenzene (DMAB) under the effect of solvents with different relative permittivities. A density functional theory (DFT) method at the B3LYP level with 6-311G++ was applied for the spectroscopic and structural analysis of the title compound. Calculations of geometric parameters (bond orders, bond lengths, and dihedral angles), electron densities, thermodynamic parameters, and orbital energies were performed for the title compound. Mulliken population analysis (MPA) as well as natural population analysis (NPA) was also performed at the B3LYP level with different solvents for finding solvent effects. In order to predict the reactivity of DMAB, molecular electrostatic potential (MESP) calculations were carried out for it. For vibrational analysis, the infrared (IR) spectra were computed for the title compound at the B3LYP/6-311G++ level in the gas phase and in different solvents with good agreement to the experimental FT-IR spectrum. The different modes of vibrations were assigned using potential energy distribution (PED). The computed Raman spectra also showed appreciable agreement with the experimental recorded Raman spectrum. The electronic absorption spectra of the title compound have been computed employing DFT/B3LYP with the 6-311G++ basis set in the gas phase and in four different solvents, that is, DMSO, ethanol, acetonitrile, and water which were compared with the experimental spectra with appreciable agreement. NBO analysis was carried out for understanding the intramolecular and intermolecular bonding of the compound and the density transfer from completely filled to unfilled orbital was found. The HOMO-LUMO energies were determined for analyzing the mechanism of intramolecular charge transfer.